Microhistoria de una familia machokosh: aproximaciones a la construcción del espacio del "hogar" en Nairobi a través del relato “An ex-mas feast” - Rasgado Blas, Jacqueline (El Colegio de México, 2016)
This article looks at the construction of space and “home” in the short story “An Ex-mas Feast” which appears in the collection of short stories Say You’re One of Them, written by the Nigerian author Uwem Akpan, published inabstracts 2008. It looks at representations of Nairobi in the Kenyan novelistic genre which describe the life of the city between 1970 and 1990 as analyzed by Roger Kurtz in his book Urban Obsessions, Urban Fears: The Kenyan PostcolonialNovel in order to contextualize this short prose work. The article focuses on the changes and continuities that have been generated through representations of the city of Nairobi in the 21th century. “An Ex-mas Feast” presents the story of a street family in Nairobi. It provides an approach that is engaged with the voice of a sector which has generally been homogenized and de-historicized in the narratives of the city: the so-called chokora, street children who are living in many cities of Kenya who are considered on the one hand, as passive and marginalized subjects, victims of the Kenyan social, economic and political structure, and on the other hand, as perpetrators of crimes and generally non-productive subjects. The story can be read as an example of support of the narratives of the Kenyan postcolonial novel written between 1970 and 1990 which have tended to represent the city of Nairobi as a place of quotidian disorder, unemployment, poverty, vio-lence and juvenile delinquency. In these narratives Kenyan writers have used allegorical characters such as male criminals and female characters that deal with prostitution to portray the problems of the independent Kenya and postcolonial disillusionment. In “An Ex-mas Feast” Akpan explores these topics too. However, I argue that Akpan’s use of the children’s voices engages in a presentation of Nairobi as a place of negotiation and possibility, which differs from the approaches of postcolonial disorder and Nairobi as a place of crisis and crime as shown in the novels written between 1970 and 1990 and consequently the narrative contains different implications for the understanding of the urban space of Nairobi. Secondly, the article explores the formation of the urban space, even in cities with high social inequality and spatial polarization such as Nairobi, as not merely a consequence of the economic and political structures of the colonial and postcolonial state, but as De Certeau points out: “a product of microbe-like, singular and plural everyday practices of people who creatively remake it”. Hence, the exploration of the short story will demonstrate a family living on the street in Nairobi, from a position, apparently marginal remaking the urban order, turning the street space, a public space considered a “no place”, into their “home”, exerting the role of agents in the construction and transformation of the urban space.